PEMANFAATAN MINYAK BIJI ALPUKAT (Avocado seed oil) UNTUK SINTESIS MEMBRAN POLIURETAN (Utilization of Avocado Seed Oil for Polyurethane Membrane Synthesis) - Fitriani, Fitriani; Khairan, Khairan; Marlina, Marlina (Jurnal Hasil Penelitian Industri, 2016)
Avocado seed oil has been used for the synthesis of polyurethane membrane, which is reactedwith 1,6-hexamethylene diisocyanate (HMDI). The main objective of this research is manufacture ofpolyurethane membranes from avocado seed oil, as a filter of this membrane use as a filter of metals fromwater such as mercury (Hg) etc.. Polyurethane membrane was synthesized by the crosslink method betweenHMDI and avocado seed oil. The results showed that the optimum ratio condition HMDI and avocado seedoil is 1.8: 5 (w/v). The result showed that flux value work at the optimum condition is 88 L/m2.h.bar, withrejection coefficient of 98.87%. Analysis with Fourier Transform Infrared (FTIR) showed that of functionalN-H group at 3314.996 cm-1, and did not reveal any FTIR of -NCO functional group at 2270 cm-1. Theabsence of absorption -NCO group proves membrane synthesis was successful. Mechanical tests andDifferential Thermal Analysis (DTA) showed that the membrane was the characteristics of a hard and rigid.Scanning Electron Microscope- Energy Dispersive X-ray (SEM-EDX) assay showed that the membranesurface is not homogeneous and membrane capable for filtering heavy metals from water contaminatedwith mercury (Hg).